2016
DOI: 10.1039/c5nr06905j
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis and HHG in nanorings: their applications in logic gates and memory mass devices

Abstract: Abstract:We study the application of one nanoring driven by a laser field in different states of polarization in logic circuits. In particular we show that assigning boolean values to different state of the incident laser field and to the emitted signals, we can create logic gates such as OR, XOR and AND. We also show the possibility to make logic circuits such as half-adder and full-adder using one and two nanoring respectively. Using two nanorings we made the Toffoli gate. Finally we use the final angular mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In ref. 37 it has been shown that a QR driven by two laser elds can be used to make logic circuits to create gates for logic operations; using the results of this work, the use of QRs to fabricate qubit, qutrit, ququads and an octal system by changing the CEP of the laser is possible with a considerable improvement of the performance of the system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In ref. 37 it has been shown that a QR driven by two laser elds can be used to make logic circuits to create gates for logic operations; using the results of this work, the use of QRs to fabricate qubit, qutrit, ququads and an octal system by changing the CEP of the laser is possible with a considerable improvement of the performance of the system.…”
Section: Discussionmentioning
confidence: 87%
“…The asymptotic behavior of the last harmonics versus the intensity of the y component of the laser suggests the possibility of controlling the harmonic emission by changing either the β parameter or the phase. In ref. 37 it has been shown that a QR driven by two laser fields can be used to make logic circuits to create gates for logic operations; using the results of this work, the use of QRs to fabricate qubit, qutrit, ququads and an octal system by changing the CEP of the laser is possible with a considerable improvement of the performance of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it is possible, by using the orbital angular momentum m and the magnetic field B 0 as control knobs of an experiment, to produce filiform currents circulating in a reduced portion of the annulus. Such currents may be used in informatics technology [20,29,31,34,35,[37][38][39][40][41][42]. Furthermore, an adiabatic increase of B 0 does not induce transition amongst the levels, but pushes the electron towards large ρ.…”
Section: Static Magnetic Fieldmentioning
confidence: 99%
“…Indeed, the versatility of QRs in the design of fast operating all-optical logic gates is noteworthy and has been discussed. Thus a QR driven by a two color laser eld has been studied 8,9 as a function of the relative intensity and phase of the two color-elds; the ne tuning of these two parameters controls the presence and absence of groups of harmonics. By assigning a logic value to the presence or absence of a particular harmonic it is possible to obtain two/three/four-state logic gatesthus extending the traditional binary logicoperating in the time range of 10 À15 s, therefore in a faster range than the usual gates.…”
Section: Introductionmentioning
confidence: 99%